Can Interactive Online Training Make High School Students More Entrepreneurial? Experimental Evidence from Rwanda - Jeanne Lafortune; Todd Pugatch; José Tessada; Diego Ubfal (Institute of Labor Economics (IZA), 2022)
We study the short-run effects of a gamified online entrepreneurship training offered to high school students in Rwanda during the COVID-19 pandemic. Using a randomized controlled trial, we estimate sizeable effects of the 6-week training on entrepreneurial activity. One month after the training, participants in schools offered the training were much more likely to own a business than participants in control schools. The training induced students to participate more actively in their school's business club, to undertake more business-oriented actions, to improve their business practices, and to interact more with other youth and family members about their business ideas. We hypothesize that the training might have motivated treated students to sustain their business activities during the COVID-19 crisis.
Keywords: I21; I25; I26; J24; L26; 330; randomized control trials; online education; entrepreneurship education; COVID-19; Rwanda